2020
DOI: 10.1080/1461670x.2020.1809496
|View full text |Cite
|
Sign up to set email alerts
|

Constructing Experts Without Expertise: Fiscal Reporting in the British Press, 2010–2016

Abstract: Thi s v e r sio n is b ei n g m a d e a v ail a bl e in a c c o r d a n c e wit h p u blis h e r p olici e s.S e e h t t p://o r c a . cf. a c. u k/ p olici e s. h t ml fo r u s a g e p olici e s. Co py ri g h t a n d m o r al ri g h t s fo r p u blic a tio n s m a d e a v ail a bl e in ORCA a r e r e t ai n e d by t h e c o py ri g h t h ol d e r s .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 73 publications
0
9
0
1
Order By: Relevance
“…In economic journalism, experts and other key institutional actors, such as representatives of research institutions, banks, ministries or central banks, are often used as authoritative sources, commentators and analysts (Basu, 2018; Berry, 2019; Chadwick et al, 2020; Harjuniemi and Ampuja, 2019; Walsh, 2020). Such authoritative actors are, in the analysis of Hall et al (1978: 58) the ‘primary definers’ of news, as they are given privileged access to the media to establish a ‘ primary interpretation’ of the topic in question.…”
Section: Primary Definers and The Sphere Of Legitimate Controversymentioning
confidence: 99%
“…In economic journalism, experts and other key institutional actors, such as representatives of research institutions, banks, ministries or central banks, are often used as authoritative sources, commentators and analysts (Basu, 2018; Berry, 2019; Chadwick et al, 2020; Harjuniemi and Ampuja, 2019; Walsh, 2020). Such authoritative actors are, in the analysis of Hall et al (1978: 58) the ‘primary definers’ of news, as they are given privileged access to the media to establish a ‘ primary interpretation’ of the topic in question.…”
Section: Primary Definers and The Sphere Of Legitimate Controversymentioning
confidence: 99%
“…Chadwick ja kumppanit (2020) kiinnittävät huomiota siihen, miten journalismi hyödyntää arvovaltaisimpia talousasiantuntijoita arvioidakseen poliitikkojen talouspoliittisia päätöksiä kriittisesti. Isossa-Britanniassa toimivien taloudellisten tutkimuslaitosten medianäkyvyyttä tutkinut Walsh (2021) arvioi samaan sävyyn, että journalismissa talouden asiantuntijoiden kyky arvioida talouspolitiikkaa kumpuaa asiantuntijalaitosten oletetusta puolueettomuudesta tai itsenäisyydestä.…”
Section: Talouden Asiantuntijoiden Uskottavuuden Hierarkia Suomalaisten Talous-ja Politiikan Toimittajien Silminunclassified
“…Chadwick and colleagues (2020) argue that in journalism practice, those economic policy experts considered most independent or above partisan politics are given the ability to assess the feasibility of economic policy ideas. Similarly, Walsh (2020) argues that the perceived independence and respect of experts are essential factors when journalists evaluate their competence and credibility. In their analysis of the relationship between economic journalists and economists in Brasil, Pedroso Neto and Undurraga (2018) argue that economists tend to see the views of mainstream economists as more credible than the views of more heterodox economists.…”
Section: Journalism and Economic Expertisementioning
confidence: 99%
“…When reporting on and analysing economic policy, journalists routinely turn to economic experts representing such institutions as banks, research institutes, government agencies, think tanks and labour market organisations (Harjuniemi and Ampuja 2019;Basu 2018;Chadwick et al 2020;Walsh 2020). The scholarship on journalistic representations of the financial crisis and the ensuing euro crisis has concluded that experts played a pivotal role in providing the public with justifications regarding such economic policy ideas as austerity (Berry 2019;Cawley 2016;Vaara 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation